Novel Detection Strategy To Rapidly Evaluate the Efficacy of Antichlamydial Agents - Zhang, Yan (Antimicrob Agents Chemother, 2017)
Chlamydia trachomatis infections present a major heath burden worldwide. The conventional method used to detect C. trachomatis is laborious. In the present study, a novel strategy was utilized to evaluate the impact of antimicrobial agents on the growth of C. trachomatis and its expression of ompA promoter-driven green fluorescence protein (GFP). We demonstrate that this GFP reporter system gives a robust fluorescent display of C. trachomatis growth in human cervical epithelial cells and, further, that GFP production directly correlates to changes in ompA expression following sufficient exposure to antimicrobials. Validation with azithromycin, the first-line macrolide drug used for the treatment of C. trachomatis infection, highlights the advantages of this method over the traditional method because of its simplicity and versatility. The results indicate both that ompA is highly responsive to antimicrobials targeting the transcription and translation of C. trachomatis and that there is a correlation between changing GFP levels and C. trachomatis growth. This proof-of-concept study also reveals that the ompA-GFP system can be easily adapted to rapidly assess antimicrobial effectiveness in a high-throughput format.